MODEL KONSTRUKSI MAKNA PERAN DAN POSISI PEREMPUAN INDONESIA PELAKU KAWIN CAMPUR - Benazir Bona Pratamawaty; Deddy Mulyana; Dadang Sugiana (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2018)
This study aims to explore marriage between Indonesian women and the western men (laki-laki bule) from western culture and to describe the meaning of role and position of Indonesian women married with western men. Individual perspective on the role and gender position in marriage life is mostly influenced by neighbours, community, and family. The process of interpreting the role and gender position for Indonesian women is a part of community construction. This research deploys phenomenological perspective, particularly symbolic interactionism and the theory of the social construction of reality. Data have been collected by in-depth interviews and observation to seven Indonesian women married to western men in Jakarta selected through snowball sampling. This research found a construction meaning model related to the role and position of Indonesian women doing mix marriage. Through interaction with their husband, the informants define their role and position in marriage life which is inline with equality principle done by their husband including four different equality meaning, such as partial equality, natural equality, absolute equality, and pragmatic equality. The contribution of this study is to provide a model of construction of meaning on the role and position of Indonesian women doing mixed marriage in family and community.